2022
DOI: 10.1038/s41467-022-33152-9
|View full text |Cite
|
Sign up to set email alerts
|

The complement C3-complement factor D-C3a receptor signalling axis regulates cardiac remodelling in right ventricular failure

Abstract: Failure of the right ventricle plays a critical role in any type of heart failure. However, the mechanism remains unclear, and there is no specific therapy. Here, we show that the right ventricle predominantly expresses alternative complement pathway-related genes, including Cfd and C3aR1. Complement 3 (C3)-knockout attenuates right ventricular dysfunction and fibrosis in a mouse model of right ventricular failure. C3a is produced from C3 by the C3 convertase complex, which includes the essential component com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The role of complement in dilated cardiomyopathy is unclear, but complement activation has been implicated in various cardiovascular and cardiac diseases, and complement activation has been shown specifically to play a role in congestive heart failure [ 34 , 35 ]. Endogenous production of complement components following myocardial infarction has been shown [ 36 ], and C3 and CFD have been shown to play a role in cardiac remodeling in right heart failure in mice, where C3 and CFD deletion ameliorated heart failure [ 37 ]. It should be noted, however, that the remodeling in right heart failure due to pulmonary hypertension typically results in hypertrophy, not dilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of complement in dilated cardiomyopathy is unclear, but complement activation has been implicated in various cardiovascular and cardiac diseases, and complement activation has been shown specifically to play a role in congestive heart failure [ 34 , 35 ]. Endogenous production of complement components following myocardial infarction has been shown [ 36 ], and C3 and CFD have been shown to play a role in cardiac remodeling in right heart failure in mice, where C3 and CFD deletion ameliorated heart failure [ 37 ]. It should be noted, however, that the remodeling in right heart failure due to pulmonary hypertension typically results in hypertrophy, not dilation.…”
Section: Discussionmentioning
confidence: 99%
“…cells that did not downregulate complement activation were destroyed), complement has roles beyond cell lysis; intracellular complement activation and local complement secretion by cells is beginning to be understood as having important roles for regulating cell activities, including in endothelial cells and fibroblasts [ 38 ]. Ito et al [ 37 ], who studied RV heart failure, also observed that complement system genes are increased in healthy controls in the right versus left ventricle, and deletion of C3 did not ameliorate LV failure due to aortic constriction in mice [ 37 ], raising the possibility that complement pathway plays different roles in the left and right ventricles. Its downregulation may play a protective role in dilated cardiomyopathy, explaining why C3 deletion had no effect on LV in Ito et al, or it might be involved in the pathogenesis of dilated cardiomyopathy through dysregulation of currently unknown cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that fatty acid uptake and de novo lipogenesis in the liver decreased as a result of a deficiency of factor D in rodents 34 , which suggested that complement components potentially regulate fatty metabolism. Factor D is required to generate the C3 convertase complex and is essential for producing C3a 35 . In this study, C3a was up-regulated, which suggested that factor D also should be co-activated in the MGD, which can modify lipid metabolism in MGD.…”
Section: Discussionmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) and mitochondrial dysfunction have emerged as critical events in the alterations that occur after hypertrophic stress [3,4]. Unbalance between Excitationcontraction coupling and the mitochondrial energy supply are potential contributors to cardiac hypertrophy progression [5,6]. In addition, the Ivyspring International Publisher uptake of cytosolic calcium into the mitochondrial matrix controls crucial Krebs cycle and electron transport chain enzymes and is required for synchronizing the heart's energy supply [7].…”
Section: Introductionmentioning
confidence: 99%